Bordetella pertussis Adenylate Cyclase Toxin Disrupts Functional Integrity of Bronchial Epithelial Layers - Hasan, Shakir; Kulkarni, Nikhil Nitin; Asbjarnarson, Arni; Linhartova, Irena; Osicka, Radim; Sebo, Peter; Gudmundsson, Gudmundur H (Infection and immunity, 2018)
The airway epithelium restricts the penetration of inhaled pathogens into the underlying tissue and plays a crucial role in the innate immune defense against respiratory infections. The whooping cough agent, Bordetella pertussis, adheres to ciliated cells of the human airway epithelium and subverts its defense functions through the action of secreted toxins and other virulence factors. We examined the impact of B. pertussis infection and of adenylate cyclase toxin-hemolysin (CyaA) action on the functional integrity of human bronchial epithelial cells cultured at the air-liquid interface (ALI). B. pertussis adhesion to the apical surface of polarized pseudostratified VA10 cell layers provoked a disruption of tight junctions and caused a drop in transepithelial electrical resistance (TEER). The reduction of TEER depended on the capacity of the secreted CyaA toxin to elicit cAMP signaling in epithelial cells through its adenylyl cyclase enzyme activity. Both purified CyaA and cAMP-signaling drugs triggered a decrease in the TEER of VA10 cell layers. Toxin-produced cAMP signaling caused actin cytoskeleton rearrangement and induced mucin 5AC production and interleukin-6 (IL-6) secretion, while it inhibited the IL-17A-induced secretion of the IL-8 chemokine and of the antimicrobial peptide beta-defensin 2. These results indicate that CyaA toxin activity compromises the barrier and innate immune functions of Bordetella-infected airway epithelia.
Keywords: Whooping Cough; antimicrobial peptides; airway epithelia; bronchy; AMP cyklický; epitelové buňky; Cyclic AMP; Epithelial Cells; signální transdukce; Interleukin-6; Cytoskeleton; epithelial cells; tight junctions; immunomodulatory cytokines; Signal Transduction; Mucin 5AC; Bordetella pertussis; adenylate cyclase toxin; lidé; Humans; interleukin-6; cyclic AMP; cytoskelet; adenylátcyklasový toxin; Bronchi; pertuse; mucin 5AC; CyaA; Adenylate Cyclase Toxin